Alternative method of nature inspired geometrical design strategy for drag induced wind turbine blade morphology - Sanderasagran, A. N.; Azizuddin, Abd Aziz; Oumer, A. N.; Idris, Mat Sahat (Universiti Malaysia Pahang, 2022)
Although drag driven wind turbine is regarded as an efficient rotor for low wind speed region, design reconfiguration is a continuous process in order to improve the performance of the rotor. The main governing factor that influences the performance of the rotor is the blade morphology. Hence, this paper presents a proposed nature inspired design approach for the development of drag driven wind turbine blade morphology. The design approach framework comprise of 3 main elements namely image processing, geometrical analysis and bio-hybridization. The proposed bio-hybridized design consist of blade mainframe curve inspired by nautilus shell and barnacle on the blade surface. It is found that integration of barnacle geometries on the surface of the blade has affected the performance of the rotor. Result shows that the peak Cm is at λ = 0.55 for experimental and CFD is Cm = 0.238 and Cm = 0.253 respectively. The proposed design resulted in experimental and numerical Cp = 0.113 and Cp = 0.127 respectively at 7 m/s and λ = 0.7. The presented design technique with appropriate design bio-element provides a systematic method for engineers to model wind turbine blade morphologies.